(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This paper examines an approach to Karl R. Popper’s philosophical and epistemological proposition (philosophy of science), as a theoretical framework to analyze the links between literary and visual creativity. Popper´s methodological proposal is briefly reviewed, as well as the way his epistemological categories are linked to the creative process, enriching it as a cognitive instrument. Then thescope of this instrument as a tool for proving and predicting validity, is explored by applying it to a particular case: the creative process that led to the creation of 18 original visual works that attempt to reflect the original sounds of vowels and consonants.